Late presentation increases risk and costs of non-infectious comorbidities in people with HIV: an Italian cost impact study. Issue 1 (December 2017) - Guaraldi, Giovanni; Zona, Stefano; Menozzi, Marianna; Brothers, Thomas; Carli, Federica; Stentarelli, Chiara; Dolci, Giovanni; Santoro, Antonella; Silva, Ana; Rossi, Elisa; Falutz, Julian; Mussini, Cristina
Abstract Background Late presentation (LP) at the time of HIV diagnosis is defined as presentation with AIDS whatever the CD4 cell count or with CD4 <350 cells/mm. The objective of our study was to assess the prevalence of non-infectious comorbidities (NICM) and multimorbidity among HIV-positive individuals with and without a history of LP (HIV + LP and HIV + EP, respectively), and compare them to matched HIV-negative control participants from a community-based cohort. The secondary objective was to provide estimates and determinants of direct cost of medical care in HIV patients. Methods We performed a matched cohort study including HIV + LP and HIV + EP among people attending the Modena HIV Metabolic Clinic (MHMC) in 2014. HIV-positive participants were matched in a 1:3 ratio with HIV-negative participants from the CINECA ARNO database. Multimorbidity was defined as the concurrent presence of ≥2 NICM. Logistic regression models were constructed to evaluate associated predictors of NICM and multimorbidity. Results We analyzed 452 HIV + LP and 73 HIV + EP participants in comparison to 1575 HIV-negative controls. The mean age was 46 ± 9 years, 27.5% were women. Prevalence of NICM and multimorbidity were fourfold higher in the HIV + LP compared to the general population (p < 0.001), while HIV + EP present an intermediate risk. LP was associated with increased total costs in all age strata, but appear particularly relevant in patients above 50 years of age, after adjusting for age, multimorbidity, and antiretroviral costs. Conclusions LP with HIV infection is still very frequent in Italy, is associated with higher prevalence of NICM and multimorbidity, and contributes to higher total care costs. Encouraging early testing and access to care is still urgently needed.